Clinical relevance of impaired consciousness in accidental hypothermia: a Japanese multicenter retrospective study. Issue 1 (11th February 2022) - Fukuda, Masahiro; Nozawa, Masahiro; Okada, Yohei; Morita, Sachiko; Ehara, Naoki; Miyamae, Nobuhiro; Jo, Takaaki; Sumida, Yasuyuki; Okada, Nobunaga; Watanabe, Makoto; Tsuruoka, Ayumu; Fujimoto, Yoshihiro; et al.
Abstract : Aim: This study aimed to investigate the association between level of impaired consciousness and severe hypothermia (<28°C) and to evaluate the association between level of impaired consciousness and inhospital mortality among accidental hypothermia patients. Methods: This was a multicenter retrospective study using the J‐Point registry database, which includes data regarding patients whose core body temperature was 35.0°C or less and who were treated as accidental hypothermia in emergency departments between April 1, 2011 and March 31, 2016. We estimated adjusted odds ratios of the level of impaired consciousness for severe hypothermia less than 28°C and inhospital mortality using a logistic regression model. Results: The study included 505 of 572 patients in the J‐Point registry. Relative to mildly impaired consciousness (Glasgow Coma Scale [GCS] 13–15), the adjusted odds ratios for severe hypothermia less than 28°C were: moderate (GCS 9–12), 3.26 (95% confidence interval [CI], 1.69–6.25); and severe (GCS < 9), 4.68 (95% CI, 2.40–9.14). Relative to mildly impaired consciousness (GCS 13–15), the adjusted odds ratios for inhospital mortality were: moderate (GCS9–12), 1.65 (95% CI, 0.95–2.88); and severe (GCS < 9), 2.10 (95% CI, 1.17–3.78). Conclusion: The level of impaired consciousness in patients with accidental hypothermia was associated with severe hypothermia and inhospital mortality. Abstract : This multicenter retrospective study using the J‐Point registry database indicated that the level of impaired consciousness in patients with accidental hypothermia was associated with severe hypothermia and inhospital mortality.